Microbial Contamination in Next Generation Sequencing: Implications for Sequence-Based Analysis of Clinical Samples - Strong, Michael J. (PLoS Pathog, 2014)
The high level of accuracy and sensitivity of next generation sequencing for quantifying genetic material across organismal boundaries gives it tremendous potential for pathogen discovery and diagnosis in human disease. Despite this promise, substantial bacterial contamination is routinely found in existing human-derived RNA-seq datasets that likely arises from environmental sources. This raises the need for stringent sequencing and analysis protocols for studies investigating sequence-based microbial signatures in clinical samples.